Study on ecological awareness and performance of nursing personnel in dialysis units - Zyga, Sofia; Baroutsou, Panagiota; Prezerakos, Panagiotis; Lazakidou, Athina; Rekleiti, Maria; Malliarou, Maria M (International Journal of Advanced Nursing Studies, 2013)
Introduction: When designing new hospital construction or refurbishment can be adopted green practices both in design and in construction and operation. Objective: To explore the ecological awareness and behavior of nursing staff in a dialysis unit. Methods: This survey involved 90 Registered Nurses and Nurses’ aides of General Hospitals in the Capital (Athens) and in province of Greece (Region of Peloponnese). These individuals were given an overall anonymous self-completed questionnaire. Results: The most important finding is that 70.8% considered as mandatory an organized effort to protect the environment in their workplace. Nurses think that greater environmental awareness is obtained 37.1% by using guidelines, 23.6% with relative stimulation, and 20.2% with educational lectures, 10.1% using poster and 6.7% in view educational videos. Finally, the correlations of ecological awareness with demographic characteristics of the sample revealed that older nursing staff with more years of working experience knows about environmental management (p-value=0.012). At the same time, gender (p-value=0,030) and educational level of the nursing staff plays an important role in the knowledge of it (p-value=0,044). Conclusions: To control costs and environmental pollution guidelines for saving energy and water and the use of environmentally friendly materials should be implemented. Thus, hospitals can become more competitive by reducing the amount of natural resources used.